Potential targets for prevention and treatment of non-alcoholic fatty liver disease in adults - Braich, Jarnail S. (International Journal of Basic & Clinical Pharmacology, 2020)
Non-alcoholic fatty liver disease (NAFLD) is a common condition worldwide contributing to serious liver disorders like hepatic fibrosis and hepatocellular carcinoma. Most common of NAFLD etiology is a sedentary lifestyle and taking a high-calorie diet. Presently there is no drug available for the treatment of NAFLD and only dietary measures, increased physical activity and exercise, antioxidants are the options. In this review, detailed pathophysiology, diagnostic methods and potential targets for prevention and timely treatment of NAFLD have been described.